Study of the quality of teaching environment and learning of cardiology residents of Shahid Beheshti University of Medical Sciences based on DREEM questionnaire - Noori Frothagh, Azam; amali, Akhtar; Gourchian, Nadergholi (Researcher Bulletin of Medical Sciences, 2020)
Background: Educational environments are an integral part of the development of educational programs. Therefore, to improve the quality of clinical education environment, its status should always be evaluated. The purpose of this study was to assess the quality of teaching environment and learning the aids of cardiology residents of Shahid Beheshti University of Medical Sciences. Materials and Methods: The study was a descriptive study, which evaluates the quality of the learning environment - the teaching of cardiology residents in a full-scale way. 33 people were included in the study. The questionnaire consisted of two sections of demographic information and 50 questions in five areas of learning, professors, student perception of their academic ability, educational atmosphere, student perception of their social conditions. Face validity was determined by medical education specialists and its reliability was 0.83 in Cronbach’s alpha. Data was entered into SPSS-25 software and analyzed by descriptive methods and Independent t-test. Result: The average scores earned in five areas were 4.99 out of a total of 200 points, which was relatively favorable with a tendency towards positive. In comparison with the educational groups, there was a significant difference in the attitude toward the teacher (p<0.01) and the individual’s attitude toward their academic ability (p<0.01) between the second and third year residents. This was relatively favorable with a tendency towards positive. In comparison with the educational groups, there was a significant difference in the attitude toward the teacher (p <0.01) and the individual’s attitude toward their academic ability (p <0.01) between the second and third year residents. Conclusion: Although the quality of teaching and learning environment of the cardiology residents of Shahid Beheshti University of Medical Sciences tends to be positive and relatively favorable, but there is room for change. Therefore, the attention of the professors to create an appropriate educational environment should be emphasized on qualitative criteria in assessing the professional capabilities of the students